Driving Health Issue based on Area: Lesson Learned from Node Thai Health Nakhon Pathom - Pratumsuwan, Kesinee; Phansisri, Phiraphat (Journal of Social Work and Social Administration, 2020)
Nakhon Pathom Rajabhat University has been selected by Thai Health Promotion Foundation to be a “Node” in Nakhon Pathom province since 2016. This is a “mechanism” for seeking to identify and assist communities to be able to develop themselves. This article presents a lesson learned from the Nakhon Pathom node during the past two phases (2016-2017 and 2018-2019). There was a total of 41 community health- promoting projects, supported by the Thai Health Promotion Foundation, implemented in 7 districts of the province. These Projects tackled several issues, for example, alcohol, smoking, exercise, safe food, waste management, and accident risk management. The key success factors were found to be: (1) good management mechanism; (2) knowledge of project development, monitoring and evaluation for development, lesson learned process, and financial report-making process; (3) synergies of all network parties; and (4) strength of node. Necessary skills for the node were deemed to be policy communication, social communication, situation assessment, risk analysis and strengthening of all partners.